Electrooptical characteristics of the novelty system: ionic doped liquid crystal - conductive polymer - Mykytyuk, T.; Aksimentyeva, O.; Stakhira, P.; Cherpak, V.; Fechan, A.; Konopelnik, O.; Fomenko, V.; Hlushyk, I. (Видавництво Національного університету «Львівська політехніка», 2004)
Taking into account that ionic-doped liquid crystals are conductive and the conductance depends on dopant concentration, we suggested using ionic-doped liquid crystals as a electrolytic medium in a described configuration of cell. The application of an ionic doped liquid crystal as electrolytic medium in electrochromic device were investigated. Polyaniline is a conductive polymer and has electrochromic effect in an electrolytic medium under the applied voltage. The spectral investigation of the electrohromic effect of polyaniline was carried out in a new cell. The spectral dependences of such structure were presented on paper. An appearance of electrochromic effect was observed in a structure SnO2 – liquid crystal – polyaniline - SnO2.